Austenitic stainless steel for polymer fuel cell separators with improved contact resistance and its manufacturing method
Optimized austenitic stainless steel with controlled alloying and AC electrolytic treatment addresses the high interfacial resistance issue in polymer fuel cell separators, achieving low contact resistance and cost-effective manufacturing.
Patent Information
- Application Number
- JP2023532243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-25
- Filing Date
- 2021-11-17
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-11-17
AI Technical Summary
Conventional stainless steel separators for polymer fuel cells face challenges in achieving low interfacial contact resistance due to the formation of passive films during bright annealing, necessitating additional costly surface treatments like coating with noble metals, which increase manufacturing time and cost.
Austenitic stainless steel with optimized alloy composition and a short alternating current electrolytic treatment process is used to improve interfacial contact resistance without additional surface treatments, by controlling alloying elements and electrolytic conditions such as current density, frequency, and sulfuric acid solution parameters.
The process achieves interfacial contact resistance of 10 mΩ·cm² or less, reducing manufacturing costs and time by eliminating the need for extra coatings, thus enhancing the suitability of stainless steel for polymer fuel cell separators.
Smart Images

Figure 0007609997000001 
Figure 0007609997000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel for a separator of a polymer fuel cell and a manufacturing method thereof, and more particularly to a stainless steel for a separator of a polymer fuel cell having improved contact resistance and a manufacturing method thereof. [Background technology]
[0002] A polymer electrolyte fuel cell is a fuel cell that uses a polymer membrane with hydrogen ion exchange properties as an electrolyte. Compared to other types of fuel cells, a polymer electrolyte fuel cell has the advantages of a lower operating temperature, higher current density and power density, a shorter start-up time, and a faster response to load changes. A polymer electrolyte fuel cell is made up of a unit cell that is made up of a membrane electrode assembly (MEA) that includes an electrolyte, electrodes, and a gas diffusion layer (GDL), and a separator. A fuel cell stack is made up of multiple such unit cells connected in series.
[0003] The separator plate is a core component of the polymer electrolyte fuel cell stack and is an electrically conductive plate having a gas flow path for the anode (or cathode) on one side and a gas flow path for the cathode (or cathode) on the other side. The separator plate acts as a current collector that conducts electrons generated from the oxidizing electrode to the reducing electrode of the next cell, supports the membrane electrode assembly, and supplies fuel (hydrogen or reformed gas) and oxidant (oxygen and air) to each electrode of the fuel cell, while also acting as a flow path to remove water generated during operation of the cell.
[0004] Conventionally, graphite has been used as the material for such separators, and most separators have channels formed by mechanically processing it. However, graphite has the disadvantage of being difficult to process and expensive, making it unsuitable for mass production. For this reason, stainless steel has recently been used in consideration of production costs and weight. When stainless steel is used as the separator for polymer fuel cells, a stainless steel plate with a thickness of 0.1 mm is generally used. The stainless steel sheet is not annealed in an oxidizing atmosphere due to the difficulty of controlling coil tension after cold rolling and to prevent surface defects such as indentations, but is bright annealed in a reducing atmosphere of hydrogen and nitrogen for recrystallization and removal of residual stress. The oxide film formed during bright annealing has high resistance in itself, so a post-treatment process to improve interface contact resistance is required for use in fuel cell separators.
[0005] As a post-treatment process, a process of coating a conductive material such as gold (Au), carbon, nitride, etc. has been proposed, but this method has the problem that the manufacturing cost and manufacturing time are increased due to the additional process of coating a precious metal, etc. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Korean Patent Publication No. 10-2010-0073407 Summary of the Invention [Problem to be solved by the invention]
[0007] In order to solve the above problems, the present invention aims to provide a stainless steel for a separator of a polymer fuel cell, which can ensure improved interfacial contact resistance by only a short AC electrolytic treatment process, without the need for additional surface treatment such as a separate coating on the austenitic stainless steel, and a manufacturing method thereof. [Means for solving the problem]
[0008] The austenitic stainless steel for fuel cell separators with improved contact resistance of the present invention is characterized by comprising, by weight percentage, C: 0.1% or less (0 is excluded), Si: 3.0% or less (0 is excluded), Mn: 3.0% or less (0 is excluded), Cr: 20-30%, Ni: 8-20%, S: 0.003% or less, P: 0.03% or less, Mo: 0.6% or less (0 is excluded), Cu: 0.8% or less (0 is excluded), N: 0.1-0.3%, W: 2.0% or less (0 is excluded), with the remainder being Fe and other unavoidable impurities.
[0009] The austenitic stainless steel of the present invention can contain, by weight percent, W: 0.01 to 0.5%. The austenitic stainless steel has an interface contact resistance of 10 mΩ cm 2 (100N / cm 2 ) or less.
[0010] The method for producing an austenitic stainless steel for a fuel cell separator having improved contact resistance according to the present invention comprises, by weight percent, C: 0.1% or less (excluding 0), Si: 3.0% or less (excluding 0), Mn: 3.0% or less (excluding 0), Cr: 20-30%, Ni: 8-20%, S: 0.003% or less, P: 0.03% or less, Mo: 0.6% or less (excluding 0), Cu: 0.8% or less (excluding 0), N: 0.1-0.3%, W: 2.0% or less (excluding 0), the balance being Fe and other unavoidable impurities, and includes the steps of bright annealing a cold-rolled material of the austenitic stainless steel, and subjecting the bright-annealed cold-rolled material to AC electrolysis in a sulfuric acid solution, the AC electrolysis being performed at 15-30 A / dm 2 The current density is applied for 7 to 10 seconds.
[0011] The austenitic stainless steel of the present invention can contain, by weight percent, W: 0.01 to 0.5%. The bright annealing step in the present invention is preferably carried out at a temperature of 1050°C to 1150°C. The temperature of the sulfuric acid solution is preferably 40 to 80°C. The concentration of the sulfuric acid solution is preferably 50 to 300 g / L. The frequency of the alternating current may be 10 to 120 Hz. Effect of the Invention
[0012] According to an embodiment of the present invention, the present invention provides a stainless steel for a separator of a polymer fuel cell, which has improved contact resistance by optimizing electrolytic treatment conditions, and a method for manufacturing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, preferred embodiments of the present invention will be described. However, the embodiments of the present invention can be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. The terms used in this application are only used to describe specific examples. For example, singular expressions include plural expressions unless the context clearly requires the singular. In addition, it should be noted that the terms "comprise" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof.
[0014] Meanwhile, unless otherwise defined, all terms used herein should be considered to have the same meaning as that commonly understood by a person having ordinary skill in the art to which the present invention belongs. Therefore, unless clearly defined herein, specific terms should not be construed as being overly ideal or formal. In addition, in this specification, the terms "about," "substantially," and the like are used in the sense of a numerical value or close to a numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are presented, and are used to prevent unconscionable infringers from unfairly exploiting the disclosure in which precise or absolute numerical values are referred to in order to aid in the understanding of the present invention.
[0015] The austenitic stainless steel for fuel cell separators with improved contact resistance according to one embodiment of the present invention is composed of, by weight percent, C: 0.1% or less (0 is excluded), Si: 3.0% or less (0 is excluded), Mn: 3.0% or less (0 is excluded), Cr: 20-30%, Ni: 8-20%, S: 0.003% or less, P: 0.03% or less, Mo: 0.6% or less (0 is excluded), Cu: 0.8% or less (0 is excluded), N: 0.1-0.3%, W: 2.0% or less (0 is excluded), the balance being Fe and other unavoidable impurities. The reasons for limiting the composition range of each alloy element will be explained below.
[0016] The C content is 0.1% or less (excluding 0). Carbon (C) is a low-cost austenite stabilizing element that effectively suppresses the formation of delta (δ)-ferrite phase. In addition, C is an interstitial element that improves the yield strength of steel through its solid solution strengthening effect. However, if the C content is excessive, it reduces the softness, toughness, and corrosion resistance of the steel, so the upper limit is set to 0.1%. Therefore, it is preferable to control the C content to 0.1% or less (excluding 0).
[0017] The Si content is 3.0% or less (0 is excluded). Silicon (Si) is an element added as a deoxidizer during steelmaking, and when a certain amount is added, it has the effect of improving the corrosion resistance of steel by forming Si-oxide in the passive film during bright annealing. However, if the Si content is excessive, it may induce the formation of intermetallic compounds such as δ-ferrite phase and sigma phase during casting, which may result in poor hot workability, softness, and toughness of the steel. Therefore, it is preferable to control the Si content to 3.0% or less (excluding 0).
[0018] The Mn content is 3.0% or less (0 is excluded). Manganese (Mn) is an element that stabilizes the austenite phase and is effective in suppressing the formation of martensite. In addition, Mn has a lower cost than Ni and improves the cold workability of steel. However, if the Mn content is excessive, a large amount of inclusions (MnS) that reduce the hot workability, softness, and toughness of the steel are formed. Therefore, it is preferable to control the Mn content to 3.0% or less (excluding 0).
[0019] The Cr content is 20-30%. Chromium (Cr) is an element that improves corrosion resistance by forming a passive film in an oxidizing environment, and is added at 20% or more to ensure corrosion resistance in a fuel cell environment. However, excessive addition of Cr in excess of 30% may promote the formation of delta (δ) ferrite in the slab, which may reduce the hot workability of the steel. In addition, austenite becomes unstable, and a large amount of Ni must be added for phase stability, which increases costs. Therefore, it is preferable to control the Cr content range to 20-30%.
[0020] The Ni content is 8-20%. Nickel (Ni) is an element that stabilizes the austenite phase, and is added at 8% or more to suppress the formation of delta (δ)-ferrite phase and improve hot workability and cold workability. However, Ni is an expensive element, and adding a large amount of Ni increases the cost of raw materials, so the upper limit is set at 20%.
[0021] The P content is less than 0.03%, and the S content is less than 0.003%. Phosphorus (P) and sulfur (S) are harmful elements that segregate at grain boundaries and reduce corrosion resistance and hot workability, so it is advisable to control their contents as low as possible. Therefore, it is preferable to control the P content to 0.03% or less and the S content to 0.003% or less.
[0022] The Mo content is 0.6% or less (0 is excluded). Molybdenum (Mo) is an effective element for improving the corrosion resistance of stainless steel. However, Mo is an expensive element, which increases raw material costs, and adding a large amount of Mo reduces cold workability. Therefore, it is preferable to control the Mo content to 0.6% or less (excluding 0).
[0023] The Cu content is 0.8% or less (0 is excluded). Copper (Cu) is an element that stabilizes the austenite phase, inhibits the formation of martensite, improves cold workability, and is an effective element for improving the corrosion resistance of steel in a reducing environment. However, if the Cu content is excessive, there is a risk that the hot workability will be deteriorated due to solidification segregation of Cu. Therefore, it is preferable to control the Cu content range to 0.8% or less (excluding 0).
[0024] The N content is 0.1-0.3%. The more nitrogen (N) is added, the more effective it is at stabilizing the austenite phase, improving the strength of the material, so 0.1% or more should be added. However, if added in excess, it reduces the elongation rate, so the upper limit is set at 0.3%. Therefore, it is preferable to control the N content range to 0.1 to 0.3%.
[0025] The W content is 2.0% or less (0 is excluded). Tungsten (W) has the effect of increasing corrosion resistance and reducing interfacial contact resistance in the sulfuric acid atmosphere in which fuel cells operate. In particular, in an environment where sulfuric acid is concentrated, adding W and Cu at the same time can maximize corrosion resistance. However, adding too much W increases the cost price because it is an expensive element, and reduces the elongation rate of the material. Therefore, it is best to control the W content range to 2.0% or less (excluding 0). A more preferable lower limit of the W content is 0.01%, and a more preferable upper limit is 0.5%.
[0026] The remaining component of the present invention is iron (Fe). However, since unintended impurities may be inevitably mixed from raw materials or the surrounding environment during normal manufacturing processes, it is not possible to exclude them. Since these impurities are known to anyone skilled in normal manufacturing processes, not all of the contents will be specifically mentioned in this specification.
[0027] During fuel cell operation, the separator plate serves as an electrical path through which electrons generated and consumed at each electrode pass, so the electrical conductivity between the separator plate and the gas diffusion layer must be good. In other words, since the electrical resistance of the separator plate closely affects the fuel cell performance, the interfacial contact resistance of the material used for the separator plate must be kept low within an acceptable level. Due to these functional requirements for the separator, the U.S. Department of Energy (DOE) has set a limit of 10 mΩ cm for the interface contact resistance of the separator. 2 (100~150N / cm 2 ) presents the following goals: The austenitic stainless steel according to one embodiment of the present invention has an interface contact resistance of 10 mΩ cm 2 (100N / cm 2 ) or less.
[0028] An austenitic stainless steel according to one embodiment of the present invention is produced by the following method. The present invention includes a step of bright annealing a cold-rolled material of austenitic stainless steel, the cold-rolled material being composed of, by weight percent, C: 0.1% or less (0 is excluded), Si: 3.0% or less (0 is excluded), Mn: 3.0% or less (0 is excluded), Cr: 20 to 30%, Ni: 8 to 20%, S: 0.003% or less, P: 0.03% or less, Mo: 0.6% or less (0 is excluded), Cu: 0.8% or less (0 is excluded), N: 0.1 to 0.3%, W: 2.0% or less (0 is excluded), the balance being Fe and other unavoidable impurities, and a step of subjecting the bright-annealed material to alternating current electrolysis in a sulfuric acid solution, the alternating current electrolysis being performed at 15 to 30 A / dm 2 This is performed by applying a current density of 100 s for 7 to 10 seconds. According to an embodiment of the present invention, the austenitic stainless steel may contain, by weight percent, W: 0.01 to 0.5%. The reasons for limiting the component ranges of each alloying element are as described above.
[0029] According to an embodiment of the present invention, the bright annealing step may be performed at a temperature of 1050°C to 1150°C. Bright annealing means annealing in a non-oxidizing atmosphere. Generally, for coils with a thickness of 0.3 mm or less, bright annealing is performed in a reducing atmosphere containing hydrogen and nitrogen to prevent surface defects and to prevent the difficulty of controlling coil tension. In this case, the hydrogen content is preferably 70% or more. In addition, the bright annealing temperature is preferably 1050 to 1150°C to prevent reoxidation of the cold-rolled austenitic stainless steel material that occurs during the heat treatment process.
[0030] Since bright annealing is performed in a reducing atmosphere, a passivation film having a thickness of several nm and a smooth surface condition is formed. Such a passivation film may contain Cr-Fe oxides, Mn oxides, and Si oxides. Cold-rolled materials that have undergone the bright annealing step have increased interface contact resistance due to a passivation film several nanometers thick formed on their surface. Therefore, in order to use bright-annealed cold-rolled materials in fuel cell separators, the non-conductive passivation film on the surface must be removed and a new conductive film must be formed.
[0031] Meanwhile, the flow of electricity, that is, electric current, can be broadly divided into direct current and alternating current. Alternating current is a flow of electricity whose direction and magnitude change periodically over time. Electrolysis, also known as electrolysis, is the process in which a chemical change occurs when an electric current is passed through an electrolyte solution, causing a substance to decompose. Depending on the type of power source, electrolysis can be broadly divided into direct current electrolysis and alternating current electrolysis. In the case of alternating current electrolysis, an electrode becomes an anode at one moment and a cathode at the next, and oxidation and reduction reactions occur continuously at a single electrode. When applying DC electrolysis to modify the surface of austenitic stainless steel, it was difficult to use it as a material for fuel cell separators due to the high interfacial contact resistance of stainless steel. After examining various control conditions to solve this problem, it was decided to introduce an AC power supply. According to one embodiment of the present invention, a bright annealed cold-rolled austenitic stainless steel material is subjected to AC electrolysis in a sulfuric acid solution to remove a passivation film and form a conductive film with improved interfacial contact resistance.
[0032] In the present invention, the waveform of the AC power supply may be any waveform such as a sine wave, a square wave, a triangle wave, or a sawtooth wave. On the other hand, the applied current density is 15A / dm 2 If the current density is less than 15A / dm, the bright annealing film cannot be removed smoothly. If the current density is too high, the effect of removing the passivation film will reach saturation, and side reactions such as oxygen generation reactions may occur, or surface erosion may occur due to excessive pickling. The applied current density should be 15-30A / dm 2 It is preferable to control the temperature to . According to one embodiment of the present invention, the frequency of the applied AC current may be 10 to 120 Hz. If the frequency of the applied AC is less than 10 Hz, the reforming efficiency decreases, so it is preferable to apply the AC at a frequency of 10 to 120 Hz.
[0033] According to an embodiment of the present invention, AC electrolysis is preferably performed for 7 to 10 seconds. If the AC electrolysis time is less than 7 seconds, the pickling effect of the hot-rolled annealed steel sheet cannot be ensured, and if the AC electrolysis time exceeds 10 seconds, it is difficult to ensure process efficiency. According to an embodiment of the present invention, the temperature of the sulfuric acid solution is preferably 40 to 80°C. If the temperature of the sulfuric acid solution is less than 40° C., the efficiency of removing the passive film decreases. The upper limit temperature is preferably limited to 80° C. for safety reasons.
[0034] According to an embodiment of the present invention, the concentration of the sulfuric acid solution may be 50 to 300 g / L. If the concentration of the sulfuric acid solution is lower than 50 g / L, the conductivity of the solution may decrease, resulting in insufficient removal of the passive film. On the other hand, even if the concentration of the sulfuric acid is increased, the effect of removing the passive film reaches saturation. Considering the economic efficiency of the electrolytic treatment, it is preferable to limit the concentration to 300 g / L. The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are merely for illustrating and explaining the present invention in more detail, and are not intended to limit the scope of the present invention, as the scope of the present invention is determined by the matters described in the claims and matters reasonably inferred therefrom. EXAMPLES
[0035] For various alloy composition ranges shown in Table 1 below, slabs were produced by continuous casting, heated at 1,250°C for 2 hours, hot rolled, and then hot rolled and annealed at 1,100°C for 90 seconds. Then, cold rolled with a reduction of 70% and bright annealed at 1,050°C.
[0036] [Table 1]
[0037] Next, electrolysis was performed under the conditions in Table 2 below, and the interfacial contact resistance value under each condition was measured. 2 Cut the sheet into two pieces by area, and place a 4 cm square tube between them to be used as the gas diffusion layer. 2 A carbon paper (SGL-10BA) of 100N / cm was placed on the surface and the contact pressure was 100N / cm 2 The interfacial contact resistance at each temperature was measured five times.
[0038] [Table 2]
[0039] Referring to Table 2, in Examples 1 to 7, when electrolysis was performed under the conditions of the sulfuric acid solution and applied current proposed by the present invention, the interfacial contact resistance was 10 mΩ cm 2 I was able to do the following: In comparison, in Comparative Example 1, the surface modification effect decreased at an applied frequency of 5 Hz, resulting in an interface contact resistance of 25.5 mΩ cm 2 was measured slightly higher. In Comparative Example 2, DC electrolysis was performed instead of AC electrolysis, resulting in a resistance of 52.5 mΩ cm 2 It has a high interfacial contact resistance. Comparative Examples 3 and 4 are 15A / dm 2 The lower applied current density did not result in removal of the bright annealed film, and the 10 mΩ cm 2 The interface contact resistance is high, exceeding . In Comparative Example 5, the temperature of the sulfuric acid solution was less than 40°C, and the bright annealed film was not sufficiently removed, resulting in a resistance of 31.7 mΩ cm 2 A high interfacial contact resistance was observed.
[0040] According to the disclosed embodiment, the contact resistance is reduced to 10 mΩ cm by optimizing the current density and frequency conditions during the electrolytic treatment without additional surface treatment such as a separate coating. 2 The following can be ensured and applied to the material for polymer fuel cell separators.
[0041] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by those skilled in the art without departing from the concept and scope of the following claims. [Industrial Applicability]
[0042] The austenitic stainless steel for fuel cell separators according to the present invention has improved contact resistance by optimizing electrolytic treatment conditions, which eliminates the need for additional post-treatment processes and reduces manufacturing costs and time, making it industrially applicable.
Claims
1. In weight percent, it consists of C: 0.1% or less (0 is excluded), Si: 3.0% or less (0 is excluded), Mn: 3.0% or less (0 is excluded), Cr: 20-30%, Ni: 8-20%, S: 0.003% or less, P: 0.03% or less, Mo: 0.6% or less (0 is excluded), Cu: 0.8% or less (0 is excluded), N: 0.1-0.3%, W: 2.0% or less (0 is excluded), the balance being Fe and other unavoidable impurities. An austenitic stainless steel for a fuel cell separator plate, characterized in that the interface contact resistance is 10 mΩ·cm 2 (100 N / cm 2 ) or less.
2. 2. The austenitic stainless steel for a fuel cell separator according to claim 1, wherein the austenitic stainless steel contains, by weight percent, W: 0.01 to 0.5%.
3. bright annealing a cold-rolled austenitic stainless steel material consisting of, by weight percent, C: 0.1% or less (0 is excluded), Si: 3.0% or less (0 is excluded), Mn: 3.0% or less (0 is excluded), Cr: 20-30%, Ni: 8-20%, S: 0.003% or less, P: 0.03% or less, Mo: 0.6% or less (0 is excluded), Cu: 0.8% or less (0 is excluded), N: 0.1-0.3%, W: 2.0% or less (0 is excluded), the balance being Fe and other unavoidable impurities; and subjecting the bright annealed cold rolled material to alternating current electrolysis in a sulfuric acid solution; The AC electrolysis is 15 to 30 A / dm 2 for 7 to 10 seconds, and the interfacial contact resistance is 10 mΩ·cm 2 (100 N / cm 2 ) or less.
4. 4. The method for producing an austenitic stainless steel for a fuel cell separator according to claim 3, wherein the austenitic stainless steel contains, by weight percent, W: 0.01 to 0.5%.
5. 4. The method of claim 3, wherein the bright annealing is performed at a temperature of 1050.degree. C. to 1150.degree. C.
6. 4. The method for producing an austenitic stainless steel for a fuel cell separator according to claim 3, wherein the temperature of the sulfuric acid solution is 40 to 80.degree.
7. 4. The method for producing an austenitic stainless steel for a fuel cell separator according to claim 3, wherein the concentration of the sulfuric acid solution is 50 to 300 g / L.
8. 4. The method for producing an austenitic stainless steel for a fuel cell separator according to claim 3, wherein the frequency of the AC current is 10 to 120 Hz.
Citation Information
Patent Citations
Sheet stainless steel for separators in solid polymer fuel cells, and solid polymer fuel cells using the same
JP2010138487A
Stainless steel for polymer electrolyte fuel cell separator and method for producing the same
JP2013117039A
Method for pickling low chrome ferritic stainless steel
KR1020100073407A
Austenitic stainless steel sheet for fuel cell separator, and method for producing same
WO2020153117A1